2015
DOI: 10.1111/iep.12142
|View full text |Cite
|
Sign up to set email alerts
|

Changes in calsequestrin, TNF‐α, TGF‐β and MyoD levels during the progression of skeletal muscle dystrophy in mdx mice: a comparative analysis of the quadriceps, diaphragm and intrinsic laryngeal muscles

Abstract: In Duchenne muscular dystrophy (DMD), the search for new biomarkers to follow the evolution of the disease is of fundamental importance in the light of the evolving gene and pharmacological therapies. In addition to the lack of dystrophin, secondary events including changes in calcium levels, inflammation and fibrosis greatly contribute to DMD progression and the molecules involved in these events may represent potential biomarkers. In this study, we performed a comparative evaluation of the progression of dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
4
19
1
Order By: Relevance
“…We observed a leftward shift in the frequency distribution of dystrophic muscle fibre size and a concomitant increase in the variability of fibre size. These observations are consistent with and extend our previous findings [12,17] and those of others [49,50], revealing substantial diaphragm muscle pathology in young (8 week old) mdx mice.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a leftward shift in the frequency distribution of dystrophic muscle fibre size and a concomitant increase in the variability of fibre size. These observations are consistent with and extend our previous findings [12,17] and those of others [49,50], revealing substantial diaphragm muscle pathology in young (8 week old) mdx mice.…”
Section: Discussionsupporting
confidence: 93%
“…) and mdx mice (Barros Maranhão et al . ). Inflammation occurs due to muscle fibre damage as a result of dystrophin deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the inflammatory process, it has been reported that inflammatory cytokines such as tumor necrosis factor α (TNF-α) and interleukin-1β (IL-1β) play a major role in the DMD phenotype [ 5 ]. In mdx mice, the experimental model of DMD [ 6 ], the TNF-α content has been well characterized and shown to have increased in the diaphragm muscle where inflammation is generally greater in this model [ 7 9 ]. The IL-1β also contributes towards muscular dystrophy, leading to the initiation and continuation of the muscle pathology in DMD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%